IMPLEMENTASI PSIKOEDUKASI TOILET TRAINING MELALUI DEMONTRASI VIDEO DAN FLASH CARD TERHADAP PENINGKATAN PENGETAHUAN IBU DAN KEMAMPUAN TOILET TRAINING ANAK TODDLER DI SEKOLAH TODDLER HARAPAN BUNDA - Machmudah, Machmudah (Universitas Nahdatul Ulama Surabaya, 2017)
The purpose of this research is to determine whether Psychoeducation with media video and flash card can increase mother knowledge and Toilet Training ability for toddler . It is a quantitative research. This research is Queasy Experiment with pre and post test control group design non randomized.. The population was devided into two group, experimental group and control group. It was all toddlers in informal school play group. The total sample is 30 toddlers. It was divided into two groups using purposive totally sampling technique. The data collection technique was : 1. Mother Knowledge Scale; 2. Observation sheet about toilet training ability; and 3. Elimination toddler schedule in 24 hours. The analyzed of date using Mann Whitney U Test & Wilcoxon Rank Test with a signifikansi 5% (α = 0,05). The finding research showed that there was influence and Psychoeducation with demontration media video and flash card toward increasing mother knowledge and toilet training ability for toddler. There was significant improvement (influence) in p value = 0.001 (p value < 0.05).this result gave recomendation for play group and parents to give modeling media video and flash card about toilet training to increase mother knowledge and ability toilet training toddler.